A Class of Numerical Methods for the Solution of Fourth-Order Ordinary Differential Equations in Polar Coordinates. (15th March 2012) - Talwar, Jyoti; Mohanty, R. K.
Abstract : In this piece of work using only three grid points, we propose two sets of numerical methods in a coupled manner for the solution of fourth-order ordinary differential equation u i v ( x ) = f ( x, u ( x ), u ′ ( x ), u ′′ ( x ), u ′′′ ( x ) ), a < x < b, subject to boundary conditions u ( a ) = A 0, u ′ ( a ) = A 1, u ( b ) = B 0, and u ′ ( b ) = B 1, where A 0, A 1, B 0, and B 1 are real constants. We do not require to discretize the boundary conditions. The derivative of the solution is obtained as a byproduct of the discretization procedure. We use block iterative method and tridiagonal solver to obtain the solution in both cases. Convergence analysis is discussed and numerical results are provided to show the accuracy and usefulness of the proposed methods.